Ancient Manuscript Textology in the Archipelago: A Comparative Analysis of Objects, Languages, and Methods in Philological Studies - Nur Sholehah, Nova Fitri; Alfiana, Fitri Alaida; Fitria Dewi, Laila Nur; Ayu Wardani, Vika Robbiul; Aziz Khoiri, Abdul (Program Studi Sastra Jawa, Fakultas Bahasa dan Seni, Universitas Negeri Semarang, 2025)
The urgency of this research is to preserve and understand the manuscripts of the archipelago's heritage, which contain a wealth of historical, religious, and cultural values. This research aims to present a textological approach in examining the diversity of ancient manuscripts in Indonesia and their significance for the preservation of local cultural heritage. The research was conducted using qualitative methods, including literature studies that employed a textual approach, such as inventorying, manuscript description, classification, comparison, and textual criticism, to determine the original manuscript. The analysis focused on the structure, language, social context, and cultural values in each manuscript. The study's results reveal complex functions, with a predominance of Islamic elements, as evidenced by the use of Arabic and Arabic-Malay. In addition, contributions from local scripts and languages such as Old Javanese were also found, which reinforce the diversity of the archipelago's manuscripts. Linguistic diversity is a characteristic of the ancient manuscripts studied in this research, including those in Arabic, Javanese, Sundanese, Ulu, and Malay. The diversity of scripts and functions of manuscripts. The heterogeneity of scripts and functions of manuscripts requires the strengthening of textology, which is measured by uniform transliteration, editing notes, and computer collation so that the determination of the master manuscript is more effective and accurate. Thus, for preservation and utilization, prioritize risk-based conservation (including iron-ink manuscripts), digitize minor manuscripts to maintain a balanced collection, align data with the national registry through digitization, and use the results as open learning resources and to strengthen literacy